2016
DOI: 10.1016/j.actpsy.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Embodiment of abstract categories in space… grounding or mere compatibility effects? The case of politics

Abstract: In two experiments, the role played by stimulus response compatibility in driving the spatial grounding of abstract concepts is examined. In experiment 1, participants were asked to classify politics-related words appearing to the left or the right side of a computer monitor as socialist or conservative. Responses were given by pressing vertically aligned keys and thus orthogonal to the spatial information that may have been implied by the words. Responses given by left or right index finger were counterbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Overall, averting the head laterally has been found to modify the perceived social interaction between the observer and the target ( Hietanen, 2002 ). The acknowledgment of the SAB effect on an array of social judgments could also prove useful for practitioners in fields relying on person perception, namely politics ( Samochowiec et al, 2010 ; Farias et al, 2013 , 2016 ), marketing and consumer behavior ( Miesler et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, averting the head laterally has been found to modify the perceived social interaction between the observer and the target ( Hietanen, 2002 ). The acknowledgment of the SAB effect on an array of social judgments could also prove useful for practitioners in fields relying on person perception, namely politics ( Samochowiec et al, 2010 ; Farias et al, 2013 , 2016 ), marketing and consumer behavior ( Miesler et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study reported here was to examine the types of social inferences that are likely to be shaped by face and gaze orientation (left, frontal, right). To this end, we integrated a range of adjectives as possible inference categories that have been used: (a) in research documenting the spatial agency bias (Maass et al, 2009;Suitner et al, 2017); (b) in research showing the two-dimensional reduction from trait judgments of faces (Oosterhof and Todorov, 2008;Walker and Vetter, 2009); (c) in recent impression formation literature yielding a twodimensional solution (Fiske et al, 2007) comparable to research on trait judgments of faces; (d) in other face perception studies (Garcia-Marques et al, 2004;Langner et al, 2010;Ma et al, 2015;O'Reilly et al, 2016;Garrido et al, 2017), and finally, (e) in research showing the grounding of abstract categories of time and politics in a horizontal left-to-right dimension (Santiago et al, 2007;Lakens et al, 2011;Farias et al, 2013Farias et al, , 2016.…”
Section: Introductionmentioning
confidence: 97%
“…Forty-five undergraduate students (37 females; M age = 23.2, SD = 7.4; six selfreported left-handers) were recruited in exchange for course credit. Sample size was determined a priori using G*Power software package for within-subjects ANOVA with 80% power to detect an effect size of η p 2 = 0.191 or similar as in earlier studies 66 . Participants were screened to normal or corrected-to-normal visual acuity.…”
Section: Methods Experimentsmentioning
confidence: 99%
“…These words served as the input for the 10 pseudo-words set. Specifically, we re-arranged the letters of each word, taking into account the orthographic and phonologic structure of the participants language, so that the pseudo-word could be pronounced (e.g., Domingos & Garcia-Marques, 2008;Farias, Garrido, & Semin, 2016;Godinho & Garrido, 2016). For example, the pseudo-words deriving from "roldana" and "trincha" were "dolnara" and "chintra," respectively.…”
Section: Methodsmentioning
confidence: 99%